A Brief, Individualized Exercise Program at Intensities Below the Ventilatory Threshold Exerts Therapeutic Effects for Depression: A Pilot Study - Sakai, Yuri; Chen, Chong; Toyomaki, Atsuhito; Hashimoto, Naoki; Kitagawa, Kan; Inoue, Takao; Sato, Asumi; Makihara, Keisuke; Kameyama, Rie; Wakatsuki, Yumi; Udo, Niki; Shirakawa, Ryosuke; et al. (Frontiers in Behavioral Neuroscience, 2021)
Due to the fact that existing pharmacological treatments for depression are not ideal, effort has been devoted to the development of complementary, alternative therapies such as physical exercise. The antidepressant effect of exercise is well documented. However, current recommendations and prescriptions of exercise may be too demanding for depressed patients, as some complain about the design of exercise programs and depression is associated with reduced motivation and capacity to exercise. Therefore, appropriately designed, patient-friendly exercise programs may prove critical for the long-term maintenance and therapeutic effects of exercise. In this pilot study, we developed an exercise program based on patients’ individual level of ventilatory threshold (VT), a submaximal index of aerobic capacity measured by Cardiopulmonary Exercise Testing (CPX). Compared to traditional measures, CPX provides more trustable indices of aerobic capacity and more homogenous exercise prescriptions. The main episode of the program consisted of 15–25 min of cycling twice a week at an intensity that approached but never went higher than subjects’ VT (considered low to moderate in intensity). We found that in patients diagnosed with major depressive disorder or persistent depressive disorder (n = 8), the program resulted in a significant reduction in depressive symptoms at week 8, which was maintained at week 16. Meanwhile, patients’ social functioning, quality of life, and cognitive functions improved. Although we used a single arm, non-randomized design, our results suggest that even a brief, low to moderate intensity exercise program may exert therapeutic effects for depression and CPX may be a useful tool for exercise prescriptions.